1985
DOI: 10.1159/000212681
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on the Cardiovascular Responses to Isometric Exercise: A Test of Autonomic Function

Abstract: Isometric exercise, promulgated as a test of autonomic function, has not been investigated in the elderly. Increasing age does not affect the cardiovascular responses to isometric exercise. Variability studies during fatiguing isometric exercise confirm that it is a valuable test of autonomic function in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…However, ratings of speed, exactitude and concentration efforts were not significantly correlated with age. Our results agree with the lower HR varia tions which have been observed in older rather than in younger men by Furchtgott and Busemeyer [ 19] 46], and intense mus cular work during dynamic exercise [1,11,18,42,44,46] or isometric exercise [22,27,41 ]. It is worth noting that maximal HR level reached during maximal effort would de cline with age, even in trained athletes [42], Studies of P-blockers suggest that attenua tion of HR reactivity during stress might be associated with age-related changes in Padrenergic reactivity [4,7,21,26,40].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, ratings of speed, exactitude and concentration efforts were not significantly correlated with age. Our results agree with the lower HR varia tions which have been observed in older rather than in younger men by Furchtgott and Busemeyer [ 19] 46], and intense mus cular work during dynamic exercise [1,11,18,42,44,46] or isometric exercise [22,27,41 ]. It is worth noting that maximal HR level reached during maximal effort would de cline with age, even in trained athletes [42], Studies of P-blockers suggest that attenua tion of HR reactivity during stress might be associated with age-related changes in Padrenergic reactivity [4,7,21,26,40].…”
Section: Discussionsupporting
confidence: 92%
“…The rise in HR in response to a variety of physical stimuli has been shown to be significantly altered with advancing age [1,11,18,22,27,31,39,41,42,44,46,50,53]. HR variations in re sponse to mental tasks have been analyzed with aging only in a few studies [2,6,17,19,21,43].…”
Section: Introductionmentioning
confidence: 99%
“…The diastolic blood pressure should rise more than 15 mmHg; 11-15 mmHg rise is borderline. 25 The rise is relatively independent of age 30 and absent in diabetic and uremic neuropathy. There is less experience with this test, and it has not been widely studied.…”
Section: Cardiovascular Responses To Standing and 30:15mentioning
confidence: 99%
“…During isometric exercise (e.g., handgrip dynamometry), heart rate, systolic and diastolic blood pressure, and total peripheral resistance increase signi®cantly (Goldstraw and Warren 1985;Shepherd and Vanhoutte 1979). During aerobic exercise (e.g., cycling and running), cardiac output, systolic blood pressure, and heart rate increase in proportion to metabolic demand, stroke volume initially increases and then plateaus, and diastolic blood pressure typically does not change (Boggard et al 1997;Raven and Mitchell 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the cardiovascular response of older males to light isometric and aerobic exercise has been less well explored. Those studies that have examined the isometric exercise response in older individuals have shown that compared to the young, older subjects exhibit smaller increases in heart rate (Goldstraw and Warren 1985;Ordway and Wekstein 1979;Petrovsky and Lind 1975). The attenuated heart rate response of older males to isometric challenge re¯ects the well documented decreased responsiveness of aging cardiovascular tissue to b-adrenergic stimulation (Baker et al 1985;Lakatta 1993;Ng et al 1994).…”
Section: Introductionmentioning
confidence: 99%